Limited edition : prototypes, one-offs and design art furniture - Lovell, Sophie (Basel, Switzerland Boston, Massachusetts : Birkhauser, 2009)
Limited edition is the new buzzword in furniture design. This title pursues this new trend in furniture design and uncovers its background in meticulous investigative essays based on the author's ongoing interchange with designers, gallery owners, and manufacturers
1. Prototypes -- 2. One-offs -- 3. Edition X -- 4. The new patrons -- 5. Auctions and Attitudes -- 6. Contributors
Keywords: Furniture design -- History -- 20th century; Furniture design -- 21st century; Furniture -- History -- 20th century; Furniture -- History -- 21st century